2011
DOI: 10.1080/08927014.2011.597051
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic waves increase the susceptibility ofPseudomonas aeruginosabiofilms to antibiotic treatment

Abstract: Bacterial urinary tract infections resulting from prolonged patient catheterization have become a major health problem. One of the major issues is bacterial resistance to antibiotic treatments due to biofilm formation inside the catheters, thus enhancing the search for alternative treatments. In the present study, a device containing a piezo element capable of transmitting low-frequency surface acoustic waves (SAW) onto the indwelling catheter was used. The SAW were able to eradicate biofilm-residing bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…After 3 weeks, this approach significantly reduced the bacterial burden in urine. Surface acous-tic waves have also been proposed for the eradication of biofilms, in conjunction with antibiotics (293).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…After 3 weeks, this approach significantly reduced the bacterial burden in urine. Surface acous-tic waves have also been proposed for the eradication of biofilms, in conjunction with antibiotics (293).…”
Section: Targeting Biofilm Recalcitrance: Progress and Perspectivesmentioning
confidence: 99%
“…It is also suggested that mechanical damage, abrogation of bacterial adhesion, and bypassing the obstacle of conditioning-films are also possible effects of ultrasound therapy (54-58). However, the major practical disadvantages of ultrasound therapy are cavitation-induced tissue damage and localized tissue heating (50). In addition, ultrasound requires professionally trained staff, relatively large instruments, and is not yet available for use on indwelling devices.…”
Section: Discussionmentioning
confidence: 99%
“…One promising approach utilized is ultrasound combined with antibiotic treatment (50). Ultrasound approach is based on longitudinal and/or shear waves through the material with linear particle motion in a cavitation range (50). It has been shown that ultrasound treatment reduces the final drug concentration needed to achieve desired microbial inhibition and minimize the generation of antimicrobial resistance among microbes (51)(52)(53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations